2021
DOI: 10.1007/s00410-021-01864-8
|View full text |Cite
|
Sign up to set email alerts
|

Formation pathways of oriented magnetite micro-inclusions in plagioclase from oceanic gabbro

Abstract: Plagioclase hosted needle- and lath-shaped magnetite micro-inclusions from oceanic gabbro dredged at the mid-Atlantic ridge at 13° 01–02′ N, 44° 52′ W were investigated to constrain their formation pathway. Their genesis is discussed in the light of petrography, mineral chemistry, and new data from transmission electron microscopy (TEM). The magnetite micro-inclusions show systematic crystallographic and shape orientation relationships with the plagioclase host. Direct TEM observation and selected area electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 57 publications
4
11
0
Order By: Relevance
“…The plagioclase hosted magnetite inclusions of the studied samples most likely formed by exsolution from iron bearing plagioclase during the sub-solidus evolution of the gabbro (Bian et al, 2021;Usui et al, 2006).…”
Section: Inclusion Originmentioning
confidence: 98%
See 2 more Smart Citations
“…The plagioclase hosted magnetite inclusions of the studied samples most likely formed by exsolution from iron bearing plagioclase during the sub-solidus evolution of the gabbro (Bian et al, 2021;Usui et al, 2006).…”
Section: Inclusion Originmentioning
confidence: 98%
“…The albite and pericline twins are polysynthetic and are regarded as transformation or deformation twins. Bian et al (2021) argued that the magnetite inclusions formed during or after transformation twinning. As a consequence, several shape orientation variants of the eight orientation classes may occur within a twinned plagioclase Note.…”
Section: Effect Of Plagioclase Twinningmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of preserved garnet and precipitate chemistry from UHP gneiss of the Central Maine Terrane (USA) shows that loss of Na and gain of Mg and Al following majoritic garnet substitution vectors during open‐system precipitation results in balanced garnet chemical formulae (Keller & Ague, 2020). Open‐system precipitation of oxide exsolutions from plagioclase is supported by chemical and crystallographic data (Bian et al, 2021). Moreover, open‐system behaviour has been demonstrated unequivocally in sulphide systems during solid‐state exsolution (Adegoke et al, 2021).…”
Section: Discussionmentioning
confidence: 86%
“…In a similar manner, oxide needles preferentially elongated along directions of similar oxygen packing, and crystallographic plane spacing to host plagioclase have been noted (Ageeva et al, 2020). These characteristics are taken as evidence of an exsolution origin (Bian et al, 2021). Experimental studies of exsolution induced in laboratory settings have shown coherent structural matches parallel to long axes of lath‐ or needle‐shaped precipitates (e.g., Bailey, 1963; Phillips et al, 1980a; Weatherly & Nicholson, 1968; Winkelman et al, 2007).…”
Section: Discussionmentioning
confidence: 99%